1988
DOI: 10.1677/joe.0.1160137
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral progesterone concentrations in the luteal-phase ewe: effects of a β-adrenergic receptor antagonist and two β2-adrenergic agonists

Abstract: Peripheral blood samples were collected at 10-min intervals from three conscious sheep in which ovulation had been induced 6-10 days previously using exogenous hormones. Saline was infused into a jugular vein for about 1 h, followed by the experimental drug for 1-2 h and followed by saline again for a further 2 h. The experiments were repeated following induced luteolysis and ovulation. The infusion of a beta-adrenergic antagonist (propranolol) into three conscious luteal-phase ewes decreased (P less than 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…Following antioxidant administration, the murine ovarian transcriptome reflected an environment with enhanced cell survival and β-adrenergic signaling, decreased apoptotic signaling proinflammatory pathways, and altered antioxidant signaling compared to control aged mice. Upregulated β-adrenergic signaling may contribute to improved ovarian function through changes in follicular development and hormone secretion [37][38][39], particularly since ovarian sympathetic nerve activity may decline with ovarian aging [40]. The anti-inflammatory effects of antioxidant treatment are consistent with previous reports [41].…”
Section: Discussionsupporting
confidence: 81%
“…Following antioxidant administration, the murine ovarian transcriptome reflected an environment with enhanced cell survival and β-adrenergic signaling, decreased apoptotic signaling proinflammatory pathways, and altered antioxidant signaling compared to control aged mice. Upregulated β-adrenergic signaling may contribute to improved ovarian function through changes in follicular development and hormone secretion [37][38][39], particularly since ovarian sympathetic nerve activity may decline with ovarian aging [40]. The anti-inflammatory effects of antioxidant treatment are consistent with previous reports [41].…”
Section: Discussionsupporting
confidence: 81%
“…Further support for the role of catecholamines in luteal function has been demonstrated in vivo by Weiss, Dail & Ratner (1982) who found that electrical stimulation of the superior ovarian nerve enhanced progesterone production in the rat, and also by Burden & Lawrence (1977) who reported that denervation or chemical sympathectomy decreased 3ß-hydroxysteroid dehydrogenase activity in corpora lutea of pregnant rats. Additionally, administration of ß-adrenergic agonists or antagonists to luteal phase ewes modulates progesterone secretion (Wheeler, Lean & Walker, 1988). In our study, there was no direct relationship between noradrenaline or dopa¬ mine and progesterone concentrations in individual corpora lutea.…”
Section: Discussioncontrasting
confidence: 66%
“…Studies in vitro with different ovarian cells revealed that catecholamines act on target cells via 8-receptors. Thls was also shown in vivo (Wheeler et al 1988;Skarzynski and Kotwica 1993) and by 38-HSD activation (Jones et al 1983) to stimulate steroidogenesis. LH is the luteotrophic hormone in ruminants (Baird 1992), but NA gtven in conscious heifers did not affect LH concentrations .…”
mentioning
confidence: 91%